From promises to action: Strengthening global commitments to fight hunger and food insecurity - Menon, Purnima; Resnick, Danielle; Zorbas, Christina; Martin, Will; Vos, Rob; Jones, Eleanor; Suri, Shoba; Iruhiriye, Elyse; Headey, Derek D.; Arndt, Channing; Fritschel, Heidi (International Food Policy Research Institute, 2024)
Since the Sustainable Development Goals (SDGs) were adopted by the United Nations General Assembly in 2015, heads of state and ministers at global convenings have repeatedly expressed commitments in support of achieving SDG2 — Zero Hunger — by 2030. Yet progress toward SDG2 has stalled, owing to economic slowdowns, unforeseen crises, geopolitical conflict, and lackluster investment in agricultural productivity and open trade.